Code Switching in Jika Kita Tak Pernah Jadi Apa-Apa Novel - Ni Kadek Dwi Juniari; Ni Nyoman Deni Ariyaningsih; I Made Iwan Indrawan Jendra (ID Solutions, 2021)
Abstract- This study has aims; (1) to classify the types of code switching found in Jika Kita Tak Pernah Jadi Apa-Apa novel and (2) to analyze the reasons. It used descriptive qualitative method in order to identify the data. The code switching was described according to theory proposed in Appel and Muysken (1987) namely to classify the types and the theory by Hoffman (1991) to describe the reasons. The result shows that all types with only 4 reasons for code switching were found in this novel types of code switching which is inter-sentential switching is the most dominant because Alvi looks more comfortable when using words, clauses and phrases in one sentence to convey motivational messages and from the result of the reason of code switching talking about a particular topic is dominant because Alvi Syahrin feels free and more comfortable to express his emotional feelings in a language that is not his everyday language.